The Investigation of Preservice Teachers’ Epistemological Beliefs, Knowledge Levels and Attitudes regarding Organ Transplantation and Donation - Gulsah Gurkan; Sibel Kahraman (Journal of Education in Science, Environment and Health)
In this study, preservice teachers' epistemological beliefs and attitude/knowledge level regarding organ transplantation and donation (OTD) are investigated according to such demographical variables as gender, department and grade level. Teachers play a fundamental role in providing information to children/adolescents and could influence their attitudes. Organ transplantation is a life-saving hope for many people around the world. But, shortage of organs for transplantation is essentially a universal problem. Having positive attitude and true knowledge to the OTD are essential for teachers that affected students the future attitude toward this topic. The research method was descriptive and cross-sectional. The sample of research was 589 preservice teachers (preschool, classroom and science teachers) in a public university in Turkey’s East. Data collection instruments were developed by researchers as valid and reliable questionnaire in order to determine the attitudes and knowledge levels of preservice teachers regarding OTD. In addition, epistemological beliefs scale which adapted to Turkish by Deryakulu and Buyukozturk (2002) was used. The results indicated the high level of knowledge and positive attitudes regarding the OTD and developed epistemological beliefs. In addition, the results of correlation matrix for relationship between attitude/knowledge and epistemological beliefs presents that developed epistemological belief has a positive effect on attitude and knowledge levels. Also, the results showed that there is a low positive relationship between attitude and knowledge level.